2012
DOI: 10.1002/bip.22080
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of caspase‐9 by stabilized peptides targeting the dimerization interface

Abstract: Caspases comprise a family of dimeric cysteine proteases that control apoptotic programmed cell death and are therefore critical in both organismal development and disease. Specific inhibition of individual caspases has been repeatedly attempted, but has not yet been attained. Caspase-9 is an upstream or initiator caspase that is regulated differently from all other caspases, as interaction with natural inhibitor XIAP-BIR3 occurs at the dimer interface maintaining caspase-9 in an inactive monomeric state. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 79 publications
1
10
0
Order By: Relevance
“…Sometimes, experiments of nature often give reasonable starting points, and to this end the dimer interface provides a point of leverage. Thus, the BIR3 domain of the endogenous caspase-9 inhibitor XIAP acts by preventing the activating dimerization of the enzyme (Shiozaki et al, 2003), and to this end peptides mimicking this interaction have been described as allosteric caspase inhibitors (Huber et al, 2012). The dimerization interface of caspases-3 and 7 contains pockets that can be utilized to block the active conformation, by an allosteric mechanism (Hardy et al, 2004).…”
Section: Synthetic Caspase Inhibitorsmentioning
confidence: 99%
“…Sometimes, experiments of nature often give reasonable starting points, and to this end the dimer interface provides a point of leverage. Thus, the BIR3 domain of the endogenous caspase-9 inhibitor XIAP acts by preventing the activating dimerization of the enzyme (Shiozaki et al, 2003), and to this end peptides mimicking this interaction have been described as allosteric caspase inhibitors (Huber et al, 2012). The dimerization interface of caspases-3 and 7 contains pockets that can be utilized to block the active conformation, by an allosteric mechanism (Hardy et al, 2004).…”
Section: Synthetic Caspase Inhibitorsmentioning
confidence: 99%
“…The findings from this study suggest that the dimeric architecture of the HYB domain is necessary to engage the Tyr(P) ligand, which is in sharp contrast to all the other known Tyr(P)-binding domains that predominantly function as monomers. Selectively targeting the dimeric interface of therapeutically important enzymes has emerged as an attractive method of allosteric inhibition (62)(63)(64)(65). The importance of the dimeric architecture of HYB in Tyr(P) substrate binding demonstrated by the present study makes it an ideal target for the design of selective allosteric inhibitors that abrogate HYB dimerization and potentially act as novel therapeutic interventions against cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Inhibition of procaspase-3 by zinc was defined upon exploration of the mechanism of activation by the chemical ligand PAC-1 (Peterson, et al, 2009) which directly competes with the caspase-3 active site for zinc. We have shown that synthetic peptide ligands can be used to modulate dimerization of caspase-9 (Huber, Ghosh, & Hardy, 2012) (exosite B, Fig. 4.0) and a small peptide, Pep419, has been developed at Genentech, which inhibits caspase-6 allosterically (Stanger, et al, 2012) (exosite G, Fig.…”
Section: Synthetic Small-molecule Inhibitors To Identify Allosterimentioning
confidence: 99%
“…Due to low sequence homology of residues comprising the dimerization interface, the size and nature of the cavity formed at this interface also varies, allowing small molecules to differentially act on this region; whether by preventing the formation of a properly-formed active site (e.g. caspase-7 (Hardy, et al, 2004a)) or by inhibiting dimerization (caspase-9 (Huber, et al, 2012) (Feldman, et al, 2012) and -8 (Feldman, et al, 2012)) (see section 4).…”
Section: Exploiting Structural Differences Amongst Caspasesmentioning
confidence: 99%
See 1 more Smart Citation